2016
DOI: 10.1186/s41038-016-0040-1
|View full text |Cite
|
Sign up to set email alerts
|

The evidence for natural therapeutics as potential anti-scarring agents in burn-related scarring

Abstract: Though survival rate following severe thermal injuries has improved, the incidence and treatment of scarring have not improved at the same speed. This review discusses the formation of scars and in particular the formation of hypertrophic scars. Further, though there is as yet no gold standard treatment for the prevention or treatment of scarring, a brief overview is included. A number of natural therapeutics have shown beneficial effects both in vivo and in vitro with the potential of becoming clinical therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 156 publications
1
19
0
1
Order By: Relevance
“…Resveratrol was discovered to be highly effective in the treatment of numerous types of tumor, including colon cancer, liver cancer and neuroendocrine tumors, as well as inflammatory reaction ( 29 , 30 ). Several previous studies have reported that resveratrol was involved in miRNA-induced autophagy during the treatment of multiple types of disease, such as chronic diabetic nephropathy ( 31 ), Alzheimer's disease ( 32 ) and cancer ( 33 ). For HSs, resveratrol has been approved as a potential agent to suppress scar formation ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol was discovered to be highly effective in the treatment of numerous types of tumor, including colon cancer, liver cancer and neuroendocrine tumors, as well as inflammatory reaction ( 29 , 30 ). Several previous studies have reported that resveratrol was involved in miRNA-induced autophagy during the treatment of multiple types of disease, such as chronic diabetic nephropathy ( 31 ), Alzheimer's disease ( 32 ) and cancer ( 33 ). For HSs, resveratrol has been approved as a potential agent to suppress scar formation ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertrophic scars are a complex pathologic process which characterized by proliferation of the dermal tissue, excessive deposition of fibroblast-derived ECM over a prolonged period and persistent inflammation and fibrosis [34]. Such pathological scarring can lead to severe functional impairment, psychological morbidity, and costly long term health care [35].…”
Section: Discussionmentioning
confidence: 99%
“…During wound healing process, the production/synthesis of collagen and GAGs act as a double-edged sword: they enhance the healing process, but excessive production or deposition may result in HS formation. Hence, the balance between degradation and synthesis of collagen plays a vital role in scarring process [18,19]. The contents of collagen (types I & III), hydroxyproline and hexosamine (GAG) were considerably decreased on topical treatment with increasing doses of BA gel (0.2 to 0.6 %).…”
Section: Discussionmentioning
confidence: 99%